Process mining support for Capability Maturity Model Integration‐based software process assessment, in principle and in practice. Issue 7 (4th February 2014) - Samalikova, J.; Kusters, R. J.; Trienekens, J. J. M.; Weijters, A. J. M. M.
ABSTRACT Currently used software process improvement methods such as the Capability Maturity Model Integration (CMMI) rely in their process assessments on information, which is gathered during interviews, in oral audit sessions, and from quality manuals and process standard reviews. Although valuable information about software processes can be gained in these assessments, the resulting data quality can be improved upon. This paper investigates the potential of process mining to support current software process assessment and improvement approaches. Based on an analysis of CMMI from a process mining perspective, particular CMMI model components are identified for which it is in principle possible to apply process mining techniques. Subsequently, criteria have been defined to select, with respect to these particular CMMI components, software processes for which process mining has an added value. These criteria have been applied in the selection of a particular 'minable' software process, that is, a change control process. Subsequently, the results of a case study from industrial practice, on the process mining of a change control board process, are used to illustrate that process mining can provide CMMI assessors with relevant information. This information reflects the actual or 'real' software processes in practice, and as such, it offers an excellent basis to support assessors in understanding the 'actual' software processes. Copyright © 2014 John Wiley & Sons, Ltd.